(3GdecJai aj Gdhba hGdGHJOGs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s
(3ChdgG (B:s
(3Chdg eHJhQ , hChd GdehLhO efg bhdg (B: (3fMh bhdg (B:" (3aGhdFc CUMGH GdfGQ ge ajgG NGdOhf (B" (3, gfG Gdhba , hdGjLhR Cf jhUd Pdc Hbhdg (B:" (3hGdPjf BefhG hYedhG GdUGdMGJ(B" s
(3BNQgG (B:s
(3hai QhGjI GdaGJMI hbd gh Gddg CMO hGdeYhPJjf , hGddg CYde SHY eQGJ Je GdcJGH GdecJai s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B254 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B653s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs